Letter (copy) : Medical supplies - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
041-0119-001 HBM/EKK/96. Social Insurance. 4th November, 1936. Messrs. W. Gimber & Son Ltd, 2, Queens Road, PECKHAM. S.E.15. Sirs, Medical Supplies. I will be very much obliged if you can send me your Catalogue for the supply of Surgical Antiseptics, surgical instruments or surgical dressings and accessories, with quotations as to the prices at which you could supply the following articles especially:- Cotton Wool, Bandages - Ordinary, different lengths, Calico, different lengths. Elastoplast, Surgical lint, Boracic lint, Common Salts, Tablets or Saline Solution, Gauze, Field Dressings, etc. I will be glad if you can send me an estimate for a small First Aid Box. Yours faithfully, Medical Adviser. 292/946/41/119